2015
DOI: 10.1080/15389588.2015.1029068
|View full text |Cite
|
Sign up to set email alerts
|

Traffic and Criminal Behavior of Adults with Attention Deficit–Hyperactivity with a Prospective Follow-Up from Birth to the Age of 40 Years

Abstract: Subjects with ADHD showed an elevated risk of being involved in criminality and had a higher risk of dying before the age of 40 years. The early detection of ADHD in childhood and appropriate treatments and family support may decrease criminality and save both money and human distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 71 publications
3
21
0
Order By: Relevance
“…Rosler et al [16, 17] found that 45% of prison inmate males and 24.5% of females have ADHD and Einat and Einat [18] found in a randomly selected cohort of Israeli adults imprisoned that 57% had ADHD. Other investigators reported on similar findings [20, 21].…”
Section: Introductionsupporting
confidence: 80%
“…Rosler et al [16, 17] found that 45% of prison inmate males and 24.5% of females have ADHD and Einat and Einat [18] found in a randomly selected cohort of Israeli adults imprisoned that 57% had ADHD. Other investigators reported on similar findings [20, 21].…”
Section: Introductionsupporting
confidence: 80%
“…It has also been reported that ADHD patients have a higher mortality risk before the age of 40, which is mainly due to accidents [8]. Several studies and meta-analyses have consistently shown that children, adolescents, and adults with ADHD have an increased overall ~1.2 to 2-fold risk of non-intentional injuries [9,10,11,12,13]. Research investigating the specific factors that contribute to this increased injury risk in ADHD patients is important, with the aim of accident prevention.…”
Section: Introductionmentioning
confidence: 99%
“…4 , 5 These problems put them at risk for failure and dropout from school, increase susceptibility to addiction disorders and criminality, and foretell poorer quality of life. 6 , 7 , 8 , 9 Given the large socioeconomic and health-care burden posed by ADHD, the development of effective and scalable therapeutics for impaired children has great practical relevance.…”
Section: Introductionmentioning
confidence: 99%